Pengaruh Struktur Aset, Pertumbuhan Penjualan, dan Ukuran Perusahaan terhadap Struktur Modal pada PT Martina Berto, Tbk - Ririn Dwi Aryanti; Nurul Huda; Aliah Pratiwi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of asset structure, sales growth, and firm size on capital structure at PT Martina Berto Tbk during the period 2014–2023. The data used in this research is secondary data, namely the financial statements of PT Martina Berto Tbk over the past ten years, obtained from the company's official website (www.martinaberto.co.id), in the form of balance sheets and income statements. The analytical methods used include classical assumption tests, multiple linear regression analysis, and hypothesis testing, conducted using SPSS version 20. The results show that asset structure, sales growth, and firm size each have a significant partial effect on capital structure. Furthermore, asset structure, sales growth, and firm size simultaneously have a significant effect on the capital structure of PT Martina Berto Tbk..